Effectiveness of the pogil model to increase learning motivation and mastery of the concept of buffer solutions students - Diana Aristiyarini; Ratu Betta Rudibyani; Tasviri Efkar; Sunyono (Asian Journal of Educational Technology, 2022)
This research aims to describe the effectiveness of the POGIL model to increase learning motivation and mastery of the concept of buffer solutions students. The research method used is quasi-experimentation with pretest-postest control group design. Sampling is done by random sampling cluster technique and obtained class XI IPA 3 as an experimental class and class XI IPA 4 as a control class. The effectiveness of the POGIL model was analyzed using the n-Gain two-average difference test to learning motivation and mastery of concepts learners' between experimental class and control class. The results of the analysis of the study data showed that the average value of n-Gain motivation learning of learners in the experimental class was greater than the control class, as well as the average grade of n-Gain mastery of concept of the experimental class was greater than the control class. The results of the influence test analysis also showed that increased learning motivation and mastery of the concept of buffer solution students were influenced by the POGIL model. It can be understood that learning with the POGIL model is effective to increase learning motivation and mastery of the concept of buffer solution students.